2012
DOI: 10.1371/journal.pone.0041266
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus in Vietnam: High Prevalence of Infection in Dialysis and Multi-Transfused Patients Involving Diverse and Novel Virus Variants

Abstract: Hepatitis C virus (HCV) is a genetically diverse pathogen infecting approximately 2–3% of the world's population. Herein, we describe results of a large, multicentre serological and molecular epidemiological study cataloguing the prevalence and genetic diversity of HCV in five regions of Vietnam; Ha Noi, Hai Phong, Da Nang, Khanh Hoa and Can Tho. Individuals (n = 8654) with varying risk factors for infection were analysed for the presence of HCV Ab/Ag and, in a subset of positive specimens, for HCV RNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 56 publications
4
51
3
Order By: Relevance
“…Dunford et al 31 found that 8.7% of commercial sex workers were HCV positive, and of those 40.2% (n=87) were non-PWIDs, but did not report data on the comparison group (non-PWID CSWs negative for HCV). Neaigus et al 27 found a positive effect but it was not statistically significant (unadjusted OR 2.0 (0.6-6.7); p=0.3; n=277).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dunford et al 31 found that 8.7% of commercial sex workers were HCV positive, and of those 40.2% (n=87) were non-PWIDs, but did not report data on the comparison group (non-PWID CSWs negative for HCV). Neaigus et al 27 found a positive effect but it was not statistically significant (unadjusted OR 2.0 (0.6-6.7); p=0.3; n=277).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Evidence of being a commercial sex worker as a risk factor for HCV infection was limited (measured in 2 studies only 27,31 ) and of very low quality (GRADE). Dunford et al 31 found that 8.7% of commercial sex workers were HCV positive, and of those 40.2% (n=87) were non-PWIDs, but did not report data on the comparison group (non-PWID CSWs negative for HCV).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Prevalence of HCV infection is markedly higher in patients on maintenance hemodialysis (MHD) [3][4][5][6][7] . Chronic HCV infection detrimentally affects the life quality, decreases life expectancy, leads to renal transplant rejection, and increases the mortality of MHD patients suffering from chronic kidney failure [1,5,6] .…”
Section: Minireviewsmentioning
confidence: 99%
“…Chronic HCV infection detrimentally affects the life quality, decreases life expectancy, leads to renal transplant rejection, and increases the mortality of MHD patients suffering from chronic kidney failure [1,5,6] . Moreover, HCV infection has been shown to increase the prevalence of renal insufficiency, defined by serum creatinine ≥ 1.5 mg/dL; the mechanisms may include the direct HCV-related renal injury and HCV-related cirrhosis with subsequent renal impairment [7] , and this will be harmful for patients who receive renal transplantation. The rates of HCV infection in MHD patients vary markedly among different countries and hospitals.…”
Section: Minireviewsmentioning
confidence: 99%
“…The prevalence of hepatitis C (HCV) virus is a public health problem, and there is a high incidence of HCV in hemodialysis (HD) patients, which affects the quality of life, life expectancy and rejection after transplantation [1,2]. Apart from the exposure to viral agents, the patients in replacement therapy units are in a constant oxidative stress process (OS) that is due to the biocompatibility of the dialyzer membrane, an imbalance of the oxidant and antioxidant systems and the effects of the dialysate components [3,4].…”
Section: Introductionmentioning
confidence: 99%